Blockchain applications on mobile device - Choo, Jian Hao (Nanyang Technological University, 2022)
Purpose - This paper will document the development of a medical electronic healthcare records (EHR) system, called MediLifeChain, in a decentralized field. The main goal is to explore the technology behind the usage of various modern software application frameworks. The focus of the exploratory will be on the use of the system with possible scalability and a unified-single source of truth in the databases. Design/methodology/approach - The React and React Native frameworks are examined and deployed with Ethereum smart contracts on the Ropsten test network and Google Firebase. It creates a vast network of features that taps on the Internet, combining both centralized and decentralized data, and transitioning the real-time data into the decentralized environment. The application will help create a secure EHR system that aims to separate the user’s personal information from the system records for security. The application allows the user to view personal health records from the different health institutions without the need to request for them as it is stored in the decentralized smart contract and centralized database. Other features include granting healthcare staff different access features and conveniently registering patients. Application testing will be conducted to ensure the application meets the need of the end-users, specifically in the medical and healthcare area. Findings - As the medical data industry grows, it becomes more interconnected and centralized databases are increasingly complex to manage with multiple sources of truth for the identity of a single patient. Many countries have already implemented the national level of EHR but there are still discrepancies for smaller clinics and third-world countries that do not have access to such a system. Originality/value - In the current year of writing this report, the rapid outbreak of COVID-19 spurs the medical system into great chaos. One of the key bottlenecks is to retrieve patient data from the database and this might lead to a matter of life-and-death situation. It further leads to the importance to have such an application that can quickly migrate the current electronic records of the healthcare information system into a decentralized manner. Thus, immediately helping to bring data across the different healthcare systems.